2017
DOI: 10.1111/aor.12997
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Increases Erythrocyte Sensitivity to Shear‐Mediated Damage

Abstract: Patients receiving mechanical circulatory support often present with heightened inflammation and free radical production associated with pre-existing conditions in addition to that which is due to blood interactions with nonbiological surfaces. The aim of this experimental laboratory study was to assess the deformability of red blood cells (RBC) previously exposed to oxygen free radicals and determine the susceptibility of these cells to mechanical forces. In the present study, RBC from 15 healthy donors were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…All these changes may affect the fragility of RBCs. For instance, McNamee et al (99) recently showed that phenazine methosulfate (an agent that generates superoxide anion within RBCs) decreased RBC deformability and increased the sensitivity of RBCs to shear-mediated damage. Hierso et al (100) compared the biophysical response of healthy and SCD RBCs to in-vitro oxidative stress, using tbutyl hydroperoxide (TBHP).…”
Section: Oxidative Stress and Rbcsmentioning
confidence: 99%
“…All these changes may affect the fragility of RBCs. For instance, McNamee et al (99) recently showed that phenazine methosulfate (an agent that generates superoxide anion within RBCs) decreased RBC deformability and increased the sensitivity of RBCs to shear-mediated damage. Hierso et al (100) compared the biophysical response of healthy and SCD RBCs to in-vitro oxidative stress, using tbutyl hydroperoxide (TBHP).…”
Section: Oxidative Stress and Rbcsmentioning
confidence: 99%
“…HBOCs in practice were expected to maintain stability in long production and storage processes . However, in the absence of an antioxidant system, including superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) , the heme iron of Hb is easily oxidized to the ferric state (methemoglobin, metHb), which cannot carry oxygen . Therefore, research on oxidation is essential to improve the capability of Hb as an HBOC.…”
mentioning
confidence: 99%
“…The impact of shear removal of membrane-bound sialic acid content may also explain the decreased RBC deformability and increased membrane rigidity observed in other studies (Horobin et al, 2017;McNamee et al, 2017;McNamee et al, 2016b;Simmonds et al, 2014;Simmonds and Meiselman, 2017). As sialic acid is negatively ionized, and cytosolic hemoglobin is positively charged, membrane-bound sialic acid is proposed to be an important regulator of hemoglobin distribution in the cytoplasm, thus also playing a role in maintaining the oxygen carrying capacity of RBCs (Huang et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 87%
“…complications have been reported with long-term use that are suggestive of blood damage and malfunction, without remarkable hemolysis. This damage, which is due to bloodinteraction with non-physiological environments (i.e., contact with foreign surfaces, elevated shear forces, turbulence and cavitation), can cause dangerous complications of altered perfusion and rheological properties of blood (Horobin et al, 2017;McNamee et al, 2017;McNamee et al, 2016b;Ruggeri et al, 2006). The observed complications of hemorrhagic events, thrombotic events, tissue ischemia and anemia, leading to multi-system organ failure (Kirklin et al, 2014), may be partially explained by altered RBC aggregation behavior.…”
Section: Accepted Manuscriptmentioning
confidence: 99%